Investigating binding energies and trapping cross-sections in an n-type Ge detector at low temperatures - Bhattarai, Sanjay; Mei, Dongming; Raut, Mathbar Singh; Panth, Rajendra; Kooi, Kyler; Mei, Hao; Wang, Guojian (Frontiers in Detector Science and Technology, 2023)
We investigated charge transport in an n-type germanium detector at 5.2 K to explore new technology for enhancing low-mass dark matter detection sensitivity. Calculations of dipole and cluster dipole state binding energies and electric field-dependent trapping cross-sections are critical to developing low-threshold detectors. The detector operates in two methods: depleting at 77K before cooling, or directly cooling to 5.2 K and applying different bias voltages. Results indicated lower binding energy of charge states in the second method, at zero field and under an electric field, suggesting different charge states formed under different operating methods.Measured cluster dipole and dipole state binding energies at zero field were 7.88±0.64 meV and 8.37±0.75 meV, respectively, signifying high low-threshold potential for low-mass dark matter searches in the future.